Analysis of the atmosphere as a narrative element in the case of films: En el nombre de la hija and Agujero negro. DOI:10.37785/nw.v4n1.a6 - Valdospinos (ORCID: 0000-0003-1688-4587), Marycruz Jimenez; Aizaga (ORCID: 0000-0002-3973-2351), Fredi Patricio Zamora (Nawi, 2020)
The art direction in a film reveals the environments in which the story takes place, in the present investigation it is tried to analyze the importance of the cinematography of the films of national production: En nombre de la hija and Agujero Negro. The theoretical framework supports the conceptual elements considering topics such as art direction and the importance of each element and narrative resource of audiovisual language in the creation of environments that are part of the cinematographic discourse. As a methodology, a mixed quantitative and qualitative approach was used. Finally, the results and interpretation will be presented, in order to issue conclusions.